Sequential, multidimensional screening - Sina Litterscheid; Dezsö Szalay (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study a sequential screening problem where the agent produces an object consisting of multiple items and has a multidimensional type that he learns over time. Depending on the strength of complementarity/substitutability of the items, the optimal allocation features a different pattern of distortions. For mild complements or substitutes, a simple solution procedure picks up the optimum.
Keywords: D80; D86; D82; 330